On the optimal ratio of surface and groundwater in water supply of the population in Ukraine - V. M. Shestopalov; N. G. Lyuta (Мінеральні ресурси України, 2024)
The Law of Ukraine “On Drinking Water, Drinking Water Supply and Sewage” contains a norm regarding “observance of an optimal balance of surface and groundwater use for drinking water supply”, although it is not defined exactly what this balance should be. At the same time, the share of groundwater in the drinking water supply of the population in Ukraine as a whole is only about 20%, and in recent decades there has been a steady tendency to reduce groundwater extraction. In European countries the share of groundwater in water supply differs significantly, but predominantly it is 65%. The share of groundwater in countries that are close to Ukraine territorially and historically is approximately the same or bigger. The territory of Ukraine is marked by complex and heterogeneous natural and anthropogenic conditions that determine the groundwater resources formation. Therefore, the optimal ratio of surface and groundwater should be determined for each administrative region. The article analyzes the provision of Ukrainian regions with forecast resources and operational reserves of groundwater, the state of their development, the ratio of surface and groundwater shares in water supply and water quality condition of groundwater deposits. A methodological approach to determining the optimal ratio of surface and groundwater in the economic and drinking water supply, taking into account the amount of groundwater, the uniformity of resource distribution and their quality characteristics, is proposed. The total percentage of groundwater in potable water supply of population in 2022 was about 23-25%. This minor part of groundwater is mainly due to the scarce groundwater extraction in the anthropogenically loaded southern regions of the country. An analysis of the quantitative and qualitative characteristics of groundwater shows that it is possible to significantly increase groundwater production even in these regions. Ukraine has considerable resources to increase groundwater production and increase its share in the population's drinking water supply. Using the already existing explored groundwater reserves of good quality can increase this share and reach a ratio of at least 50/50 in the coming years. This will have an undoubtedly positive impact on public health and will bring water sources as close as possible to consumers and ensure uninterrupted water supply in times of war.